Applying the Behavioural Intervention Technologies model to the development of a smartphone application (app) supporting young peoples' adherence to anaphylaxis action plan. Issue 2 (2nd April 2015) - Anderson, Joanna K; Wallace, Louise M
Abstract : The incidence of fatal anaphylaxis is significantly higher among young people aged 15–25 compared with other age groups. Hospital admission or fatal outcome following anaphylaxis often results from failure to adhere to an agreed anaphylaxis action plan (AAP). The main barriers for adherence include lack of confidence to recognise symptoms of severe reaction, lack of confidence and skills to correctly use an adrenaline auto-injector (AAI), and not having the AAI available when needed. We describe the development of a smart phone application (app) to increase young peoples' adherence to AAP. The development of the app was informed by information from a literature review to identify factors enhancing and impeding young peoples' adherence to their AAP, combined with data from consultations with intended users and clinicians working with young people at risk of anaphylaxis regarding their needs and expectations with regard to the content and technical features of the app. The design process was underpinned by the novel Behavioural Intervention Technologies model. This ensured that the apps' content is evidence based, complies with current guidelines, and responds to users' needs and preferences in relation to content and technical characteristics. 'Anaphylaxis' app is the first smart phone app that comprises a comprehensive personalised AAP. Since its launch in February 2013, it has been downloaded by approximately 16 000 users worldwide. Further research is required to demonstrate its effectiveness in improving self-management of anaphylactic risk in young people.